2019
DOI: 10.1002/jmor.20976
|View full text |Cite
|
Sign up to set email alerts
|

Functional morphology of the mouthparts of lady beetle Coccinella transversoguttata (Coccinellidae, Coleoptera), with reference to their feeding mechanism

Abstract: The lady beetle Coccinella transversoguttata is an important biocontrol agent of aphids. As the main the feeding apparatus, mouthparts play essential roles in feeding process, and the morphological variation of mouthparts is correlated with variation in food source and feeding behavior.To better understand the feeding behavior of C. transversoguttata, we studied the functional morphology of mouthparts, with special attention to the fine morphology of each part of mouthpart and various kinds of sensilla. The mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 30 publications
1
20
0
Order By: Relevance
“…However, in another study, the sensilla densities are very similar in two anopheline sibling species (Diptera) with different host preferences [60]. In Coleoptera, relevant studies were much rare, while the role of mouthpart sensilla in feeding process have been studied in several species [46,61,62]. We found that many types of sensilla are distributed both on antennae and mouthpart, thus more comparative studies should be done to conform if there is correlation between the number of sensilla and feeding preference.…”
Section: Antennal Sensilla Versus Host Preferencementioning
confidence: 61%
See 3 more Smart Citations
“…However, in another study, the sensilla densities are very similar in two anopheline sibling species (Diptera) with different host preferences [60]. In Coleoptera, relevant studies were much rare, while the role of mouthpart sensilla in feeding process have been studied in several species [46,61,62]. We found that many types of sensilla are distributed both on antennae and mouthpart, thus more comparative studies should be done to conform if there is correlation between the number of sensilla and feeding preference.…”
Section: Antennal Sensilla Versus Host Preferencementioning
confidence: 61%
“…Sensilla chaetica (Sch) is the most abundant sensilla in not only the antennae but also the mouthpart of H . variegata [ 46 ]. They are also universal on the antennae of many other insects [ 3 , 18 , 35 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…One example, covering all mouthparts, is the work of Schmitt et al (2014) on Periplaneta americana (Blattodea: Blattidae), describing movement patterns of the mouthparts using X-ray cinematography. Furthermore, Hao et al (2020) carried out an extensive study on the functional morphology of the mouthparts of the lady beetle Coccinella transversoguttata (Coleoptera: Coccinellidae). They focused on identifying different types of sensilla found on the mouthparts, subsequently drawing conclusions regarding their specific function.…”
mentioning
confidence: 99%